1994
DOI: 10.1128/jb.176.11.3162-3170.1994
|View full text |Cite
|
Sign up to set email alerts
|

Gonococcal transferrin-binding protein 2 facilitates but is not essential for transferrin utilization

Abstract: Pathogenic Neisseria species have been shown to scavenge iron from transferrin (Ti)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
225
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(232 citation statements)
references
References 49 publications
7
225
0
Order By: Relevance
“…gonorrboeae (Anderson et al, 1994). The absence of obvious promoter sequences in the 85 bp intercistronic region upstream of the Neisseria t b p A gene (Legrain e t al., 1993;Cornelissen e t al., 1992) suggested that the two genes might be transcribed from a single promoter ; this was confirmed by elimination of t b p A expression upon insertional mutagenesis in the tbpB gene with an C2 fragment (Anderson et al, 1994). The short 13 bp intercistronic region between the tbp genes in A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gonorrboeae (Anderson et al, 1994). The absence of obvious promoter sequences in the 85 bp intercistronic region upstream of the Neisseria t b p A gene (Legrain e t al., 1993;Cornelissen e t al., 1992) suggested that the two genes might be transcribed from a single promoter ; this was confirmed by elimination of t b p A expression upon insertional mutagenesis in the tbpB gene with an C2 fragment (Anderson et al, 1994). The short 13 bp intercistronic region between the tbp genes in A .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that tbp genes are regulated by Fur since putative Fur boxes have been identified upstream of the tbpB gene in N. meningitidis (Legrain e t al., 1993), N . gonorrboeae (Anderson et al, 1994), H. injuenqae (Gray-Owen et al, 1995) and, based on the results of the present study, A.…”
Section: Discussionmentioning
confidence: 99%
“…The TF receptor is composed of the 100 kDa transmembrane protein, Tbp1, and the 85 kDa lipoprotein, Tbp2, encoded by the genes tbpA and tbpB, respectively (Schryvers and Morris, 1988a;Cornelissen et al, 1992;Legrain et al, 1993;Anderson et al, 1994;Cornelissen and Sparling, 1994;Cornelissen and Sparling, 1996). The LF receptor is composed of the 103 kDa transmembrane protein Lbp1 and a lipoprotein, Lbp2, analogous to Tbp2 encoded by the genes lbpA and lbpB, respectively (Schryvers and Morris, 1988b;Pettersson et al, 1993;1994a,b;Biswas and Sparling, 1995;Bonnah et al, 1995;Lewis et al, 1996;our unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…We focused our efforts on two Tbp-specific domains, the NB domain from TbpB and the L2 domain from TbpA based largely on surface exposure and strain-to-strain sequence conservation. Though TbpB is considered to be fully surface exposed [42,43], we demonstrated L2 surface exposure by flow cytometric analysis. Because we utilized fixed instead of live cells in our surface binding studies, it is possible surface accessibility of the L2 domain by L2 antisera was due to non-native conformations of surface TbpA molecules [44].…”
Section: Discussionmentioning
confidence: 92%